2011
DOI: 10.1016/j.acvd.2010.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Fate of the distal aorta after surgical repair of acute DeBakey type I aortic dissection: A review

Abstract: Operated acute DeBakey type I aortic dissection has to be considered as a chronic aortic disease with the potential of late distal dilatation with aneurysm formation and need for reoperation. Several intraoperative strategies have been devised to prevent late complications. However, the increased operative risk associated with a more aggressive initial approach in an emergent setting has to be balanced against the relatively low incidence of late reoperations. Further studies will have to identify preoperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…The longer-length Dacron graft, as used for hemiarch repair, does generally serve as an excellent proximal landing zone in our experience, and this fact should probably be considered when an acute type A dissection is repaired, given that at least one-third of these patients will need an additional intervention for late-developing downstream pathology after surgery for this condition and that dilation of the distal aorta will develop in more than half. [24][25][26][27][28] Notably, to our knowledge, the two Dacron landing zone endoleaks presented here represent the first reported endoleaks in a Dacron landing zone with TEVAR. Importantly, the Dacron landing zone type I endoleak rate fell to 0% in the second and third tertiles of experience when the aforementioned policy of a minimum Dacron overlap length of >4 to 5 cm was adopted, supporting the recommendation of prior authors.…”
Section: Discussionmentioning
confidence: 57%
“…The longer-length Dacron graft, as used for hemiarch repair, does generally serve as an excellent proximal landing zone in our experience, and this fact should probably be considered when an acute type A dissection is repaired, given that at least one-third of these patients will need an additional intervention for late-developing downstream pathology after surgery for this condition and that dilation of the distal aorta will develop in more than half. [24][25][26][27][28] Notably, to our knowledge, the two Dacron landing zone endoleaks presented here represent the first reported endoleaks in a Dacron landing zone with TEVAR. Importantly, the Dacron landing zone type I endoleak rate fell to 0% in the second and third tertiles of experience when the aforementioned policy of a minimum Dacron overlap length of >4 to 5 cm was adopted, supporting the recommendation of prior authors.…”
Section: Discussionmentioning
confidence: 57%
“…The rate of enlargement of the distal aorta after dissection repair is also greater when a patent false lumen is present, 4,10,17 but the timing and rate of distal aortic expansion cannot be anticipated with any degree of accuracy, and some patients may develop aneurysmal dilation following many years of relative dimensional stability. 1,4 These observations emphasize the need for consistent lifelong surveillance in patients with repaired type-A aortic dissection to assure long-term survival because of the unpredictable nature of subsequent aneurysm development and rupture. 18 The current patient did not have routine radiologic follow-up during the 14-year period after his original dissection repair, although a CT scan obtained 6 years after his original surgery suggested the absence of aortic arch dilatation.…”
Section: Diagnosis: Large Aortic Arch Aneurysm Complicating Chronic Amentioning
confidence: 98%
“…Aneurysm formation distal to the site of a type-A aortic dissection repair is a well-known but relatively unusual complication. 1 The results of several studies clearly demonstrated that the ten-year freedom from reoperation on the distal aorta or its major branches after primary dissection repair exceeds 70% and may approach 90% in many centers. [2][3][4][5][6][7] When dilation of the distal aorta after dissection repair does occur, the aortic arch and the proximal descending thoracic aorta are most likely to be affected, 8 as was seen in the current patient.…”
Section: Diagnosis: Large Aortic Arch Aneurysm Complicating Chronic Amentioning
confidence: 99%
“…The ability to more reliably assess FL thrombosis (compared with CT) is an advantage of MRI in this context as FL thrombosis has been shown to be associated with reduced aortic expansion rates (7,10,34). Amano et al reported their series of 16 chronic thoracic aortic dissection patients who underwent MRI at 1.5 T utilizing cardiacgating, respiratory compensation, and fat suppression acquisition techniques together with 3D PC imaging of flow patterns (9,35). They demonstrated that time-resolved 3D MRI may be used to assess the presence of blood-flow within the FL which has previously been shown to be prognostically significant (35,36).…”
Section: Current Mri Technologymentioning
confidence: 99%
“…It is well recognized that persisting or chronic aortic dissection (>2 weeks after initial intimal injury) is a risk factor for further aortic dilatation and dissection extension (7)(8)(9). In these cases, intervention may be required to prevent progressive aortic dilatation (1).…”
Section: Introductionmentioning
confidence: 99%